Measuring Basic Wants for State and Local Public Goods: A Preference Independence Transformation Approach - Blackley, Paul R.; DeBoer, Larry (The Review of Economics and Statistics, 1987)
Paul R. Blackley, Larry DeBoer, Measuring Basic Wants for State and Local Public Goods: A Preference Independence Transformation Approach, The Review of Economics and Statistics, Vol. 69, No. 3 (Aug., 1987), pp. 418-425